Hookworm infection and anemia in adult women in rural Chiapas, Mexico - Brentlinger Paula E.; Capps Linnea; Denson Melinda (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To describe associations between anemia and hookworm (Necator americanus) infection in hospitalized women in rural Chiapas, Mexico. MATERIAL AND METHODS: We retrospectively reviewed the hospital records of 68 anemic women (defined as having a hemoglobin level <10mg/dl) or with intestinal parasitism, identified through hospital discharge and transfusion records for the calendar year 1999. The medical charts of 86 cases were located, 18 of which were not confirmed as anemia cases. The hospital is located in Altamirano, Chiapas. Characteristics of subjects were compared using Student's t-test (for continuous variables) and the chi2 test (for categorical variables). A p-value <0.01 was used for statistical significance. Chart review and data analysis took place during the year 2000. RESULTS: Fifty percent of women who had stool examinations were infected with N. americanus. Necator often coexisted with other potential causes of anemia, such as pregnancy and hemorrhage. Hemoglobin levels in hookworm-infected women (mean 4.1 g/dl) were significantly lower than in uninfected women (mean 7.0 gm/dl), and Necator prevalence was significantly higher in the anemic women (50%) than in the overall hospital population (1.9%). CONCLUSIONS: Anemic women should be offered stool testing where Necator is present, and should be considered for antihelminthic treatment even if pregnant. Further investigation is recommended among women in Chiapas, and probably elsewhere in Mexico.